Daily Behavior and Range of Rehabilitated Orangutan in the Hutan Pinus Jantho Nature Reserve, Aceh Besar - Hadi Sofyan; Satyawan Pudyatmoko; Muhammad Ali Imron (Jurnal Ilmu Kehutanan)
Adaptation mechanism of reintroduced Sumatran Orangutan is crucial information for successful rehabilitation program. The main objective of this research was to investigate daily behaviors and range of eight rehabilitated Orangutans in the reintroduction station of Nature Reserve Pine Forest Jantho, Aceh Besar. Data collection was conducted through instantaneous sampling to explore daily behavior and range. The daily activities data were grouped based on ethogram by adopting the standard of Orangutan‘s data collection. The result showed that the proportion of daily behavior of Orangutan Sumatera are 47.32 % resting, 37 % feeding, 14.75 % moving, 0.52 % social interaction and 0.41% nesting activities. There was no different behavior between sex classes and duration of rehabilitation. The average daily range of all focal individuals is 0.7-26.2 ha. Previous interaction with humans, especially during early developmental period, may affect in behaviour of rehabilitated Orangutan Sumatera and probably also influence the adaptation success in the wild.